A History of Molecular Level Analysis of Natural Organic Matter by FTICR Mass Spectrometry and The Paradigm Shift in Organic Geochemistry. Issue 2 (24th December 2020) - Cooper, William T.; Chanton, Jeffrey C.; D'Andrilli, Juliana; Hodgkins, Suzanne B.; Podgorski, David C.; Stenson, Alexandra C.; Tfaily, Malak M.; Wilson, Rachel M.
Abstract: Natural organic matter (NOM) is a complex mixture of biogenic molecules resulting from the deposition and transformation of plant and animal matter. It has long been recognized that NOM plays an important role in many geological, geochemical, and environmental processes. Of particular concern is the fate of NOM in response to a warming climate in environments that have historically sequestered carbon (e.g., peatlands and swamps) but may transition to net carbon emitters. In this review, we will highlight developments in the application of high‐field Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) in identifying the individual components of complex NOM mixtures, focusing primarily on the fraction that is dissolved in natural waters (dissolved organic matter or DOM). We will first provide some historical perspective on developments in FTICR technology that made molecular‐level characterizations of DOM possible. A variety of applications of the technique will then be described, followed by our view of the future of high‐field FTICR MS in carbon cycling research, including a particularly exciting metabolomic approach.